Eating sweets without the wrapper: perceptions of HIV and sexually transmitted infections among street youth in western Kenya. Issue 3 (3rd March 2016) - Embleton, Lonnie; Wachira, Juddy; Kamanda, Allan; Naanyu, Violet; Ayuku, David; Braitstein, Paula
Abstract: Street-connected youth in Kenya are a population potentially at risk of HIV transmission, yet little is known about their perceptions and experiences of sexually transmitted infections (STIs), despite their living in an HIV endemic region. We sought to elucidate the language and sociocultural factors rooted in street life that impact on street-connected young people's knowledge of and perceptions about the prevention and transmission of STIs, and their diagnosis and treatment, using qualitative methods in western Kenya. We conducted a total of 25 in-depth interviews and 5 focus-group discussions with 65 participants aged 11–24 years in Eldoret, Kenya. Thematic analysis was conducted and data were coded according to themes and patterns emergent until saturation was reached. In general, street-connected young people knew of STIs and some of the common symptoms associated with these infections. However, there were many misconceptions regarding transmission and prevention. Gender inequities were prominent, as the majority of men described women as individuals who spread STIs due to unhygienic practices, urination and multiple partners. Due to misconceptions, gender inequity and lack of access to youth-friendly healthcare there is an urgent need for community-based organisations and healthcare facilities to introduce or augment their adolescent sexual and reproductive health programmes for vulnerable young people.